Medical Skills in a Clinical Presentation-Based Curriculum: Preventive Care of the 4 Month Old - Gordon Woods (Association of American Medical Colleges, 2015)
Abstract Introduction This resource is a learning session for preclerkship medical students on providing routine preventive care for the 4-month-old infant. The instructional approach used in this learning activity guides students as they interview and advise a mother who is bringing in her 4-month-old infant for routine preventive care. The exercise challenges the students to accomplish multiple tasks during a time-limited, simulated clinical encounter. Methods During this session, students individually (or in pairs) interview a standardized mother with her 4-month-old infant (actually a life-sized doll wrapped in a baby blanket). After the encounter, students complete a SOAP (subjective, objective, assessment, and plan) note, receive feedback from the standardized patient, receive feedback from their peer observer (if present), and debrief in a group discussion with a faculty member. This resource include a readiness assurance quiz; a preparatory exam room guide and video; a summary outline that students can use during the standardized patient encounter; a check sheet to guide peer observer feedback; and a standardized patient case blueprint with two supportive forms. Results This session has been presented over the last 3 years as part of the medical skills course at the Texas Tech University Health Sciences Center Paul L. Foster School of Medicine. This session was positively reviewed by students using an online end-of-session comment form, and also at the end of the first curricular block. Discussion This resource gives students an opportunity to practice and refine their exam room communication skills. In addition, it highlights the importance of preventive care as one of the most effective, yet sometimes undervalued, aspects of patient care.